Development of a semi-active car suspension control system using magneto-rheological damper model - Rashid, M.M.; Hussain, Mohd Azlan; Rahim, N. Abd; Momoh, J.S. (International Journal of Mechanical and Materials Engineering, 2007)
In this paper, the development of a semi- active suspension control of quarter car model using fuzzy-based controller has been done. The quarter car model to be used here can be described as a nonlinear two degrees of freedom system which is subject to excitation from different road profile. The semi-active control is designed as the fuzzy control inferred by using two single input rule fuzzy modules, and the road model is used as the control force is released by actuating an electromagnetic shaker. To implement semi-active suspension system experimentally, the MR damper is used here as the adjustable damper. The MR damper is a control device that consists of a hydraulic cylinder filled with magnetically polarizable particles suspended in a liquid. MR dampers dissipate vibration by absorbing energy. Magnetorheological (MR) fluids dampers are very effective to control vibration, which use MR fluids to produce controllable damping force and provide both the reliability of passive systems and the facility of active control systems with small power supply. Due to their mechanical simplicity, high dynamic range, low power requirements, large force capacity, and robustness, offer an attractive means of vibration protection. The objectives of this are modeling of semi-active suspension system, developing controller and understanding the characteristics of the MR damper to provide effective damping for the purpose of suspension isolation or suppression car model. In this work pid, fuzzy logic and fuzzy-hybrid controller are used to control semi-active car suspension system.